الرقابة القضائية على التحكيم في دعوي الشقاق والنزاع في قانون الأحوال الشخصية الأردني رقم (15) لعام 2019 م. - الحنيطي، سناء جميل علي (جامعة آل البيت, 2022)
تناولت الدراسة موضوع الرقابة القضائية على التحكيم في دعوى الشقاق والنزاع في قانون الأحوال الشخصية الأردني رقم (15) لعام 2019،‏ لبيان مدى مراعاة المشرع الأردني للرقابة القضائية على التحكيم في قانون الأحوال الشخصية الأردني من خلال المنهج الوصفي القائم على دراسة موضوع التحكيم، وجمع المعلومات الوافية عنه، ثم اعتماد المنهج الاستقرائي وذلك بتتبع مفردات المواد القانونية لمعرفة مدى مراعاة المشرع الأردني للرقابة القضائية في إجراءات التحكيم المنصوص عليها في القانون، ثم المنهج التحليلي القائم على عرض النصوص القانونية المتعلقة بموضوع الدراسة والعمل على تحليلها وبيان الفراغات التشريعية فيها واقتراح ما يلزم من إجراءات لسدها، أملا في تحقيق العدالة القضائية في الحكم الصادر في دعوى الشقاق والنزاع والمتوقف على نتيجة تقرير الحكمين المرفوع من قبلهما للقاضي. وقد خلصت الدراسة إلى أن المشرع الأردني قد أغفل آلية الرقابة القضائية على التحكيم في دعوى الشقاق والنزاع المنصوص عليه في قانون الأحوال الشخصية. ولذا يوصي الباحث المشرع الأردني بضرورة النظر في التنظيمات التشريعية المقترحة والأخذ بها كالنظام الرقابي المقترح في هذه الدراسة من تشكيل هيئة تحكيم خاصة؛ والعمل على إيجاد دائرة تحكيم مزودة بنظام رقابي من شأنه مراقبة إجراءات التحكيم في دعوى الشقاق والنزاع والمنظورة في المحاكم الشرعية الأردنية ابتداء من انتخاب الحكمين وانتهاء بتقريرهما. The study dealt with the issue of judicial oversight of arbitration in the case of discord and dispute in the Jordanian Personal Status Law No. (15) of 2019 to show the extent to which the Jordanian legislator defers judicial oversight of arbitration in the Jordanian (15) of 2019 to show the extent to which the Jordanian legislator defers judicial oversight of arbitration in the Jordanian Personal Status Law through the descriptive method based on studying the issue of arbitration and collecting adequate information concerning it, then adopting the inductive approach by tracking the vocabulary of the legal articles to define the extent to which the Jordanian legislator defers judicial oversight in the arbitration procedures stated in the law, then the analytical approach based on presenting the legal texts related to the subject of the study and working on analyzing them and clarifying the legislative gaps in them and suggesting the necessary procedures to fill them, in the hope of achieving judicial justice in the judgment issued in the discord and dispute lawsuit which depends on the outcome of the report of the two judgments submitted by them to the judge. The study concluded that the Jordanian legislator has omitted the judicial oversight mechanism for arbitration in the discord and dispute lawsuit stated in the Personal Status Law. Therefore, the researcher recommends to the Jordanian legislator the need to consider the proposed legislative regulations and take them into account, such as the supervisory system proposed in this study by forming a special arbitration commission, and working to create an arbitration department equipped with a supervisory system that would monitor arbitration procedures in the discord and dispute lawsuit considered by the Jordanian Sharia courts, starting by electing the two judgments and ending with reporting them.
Keywords: القضاء الأردني -- الرقابة القضائية -- دعوي الشقاق والنزاع -- التحكيم بين الزوجين -- قانون الأحوال الشخصية الأردني